Домашние салаты - Сладкова Ольга Владимировна (Миллион рецептов, 2012)
Экземпляры: ф11 (20180326) / Инвентарный номер: 55660 / Цена: 30.00 / Сис.шифр: 36.991 / Авт.знак: С 47 / ГРНТИ: 75.35 / ББК: 36.991